2018
DOI: 10.30566/2600-8254.2018.2.2.1
|View full text |Cite
|
Sign up to set email alerts
|

A Cross Sectional Analysis of Socio-economic Determinants on Infant Mortality in South Asian Region

Abstract: The purpose of this study to find out the reasons behind infant mortality in South Asian countries. This problem depends on many factors. For finding the fact the study has gone through the reports of the database of World Bank and World Factbook. Using time series data (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014), the study explored the association between Infant Mortality Rate and Socio-Economic Determinants (birth attended by skill health staff, dependency ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Lamichhane, et al (2017) identified several influencing key factors of the infant mortality rate in Nepal, including birth spacing, breastfeeding, parenting styles, and ecology. In line with this, Sarkar, Dhar, and Rouhoma (2018) also found differences in the adequate number of health facilities in developed countries compared with the relative lack in developing countries, and identified several determining factors of infant mortality rates, namely delivery assistance, the education level of the mother, and total population. Most ASEAN countries are developing countries, and the infant mortality rate is still rarely studied in the ASEAN region, so it is interesting to estimate the influence of socioeconomic factors on infant mortality rate in ASEAN.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Lamichhane, et al (2017) identified several influencing key factors of the infant mortality rate in Nepal, including birth spacing, breastfeeding, parenting styles, and ecology. In line with this, Sarkar, Dhar, and Rouhoma (2018) also found differences in the adequate number of health facilities in developed countries compared with the relative lack in developing countries, and identified several determining factors of infant mortality rates, namely delivery assistance, the education level of the mother, and total population. Most ASEAN countries are developing countries, and the infant mortality rate is still rarely studied in the ASEAN region, so it is interesting to estimate the influence of socioeconomic factors on infant mortality rate in ASEAN.…”
Section: Introductionmentioning
confidence: 56%
“…The study found a positive relationship between infant mortality rate, fertility, and population domicile, while the female labor force and GDP per capita were insignificant. Sarkar, Dhar, and Rouhoma (2018) studied the influencing socioeconomic factors of infant mortality rates in several ASEAN countries and found that education level, delivery assistance by medical personnel, and the population had a significant influence on infant mortality rate. Goldani, et.al (2001) found that social inequality had an influence on the infant mortality rate in Brazil.…”
Section: Literature Reviewmentioning
confidence: 99%
“…During his assessment, he exhibited that a 3% increase in RGDP was linked with a 1%-point lessening in the rate of unemployment. According to Sarkar et al (2018), this study suggests that, in South Asian countries, the growth rate of population, literacy rate, and birth attended by skill health staff affect much for the infant deathrate rate (mortality rate) instead of dependency ratio, mother's mean age initially birth and poverty. From the study is it vibrant that overpopulation creates most of the issues comprising unemployment etc.…”
Section: Literature Reviewmentioning
confidence: 97%
“…In 1970s, in accordance with the argument of the authors of [5], who underlined that through investing in education and health, a person aims to increase his/her future income, the authors of [6] redefined the term human capital as 'a combination of innate capabilities as well as acquired skills, knowledge and motivation that are used for producing goods and services and represent a source of human and social income', which consequently improves productivity and thus economic growth [7]. Later, with the rise of the Endogenous Growth Theory during 1980s, which differs from neoclassical growth through emphasizing that economic growth is not a result of forces that impinge from the outside, but an endogenous outcome of an economic system [8] generated as a direct result of internal processes such as human Sustainability 2024, 16, 3898 2 of 30 capital, innovation and technical progress, the importance of human capital on economic growth and development started to receive accelerating attention theoretically and empirically, leading to a strong consensus on the significance of human capital accumulation for economic growth (among many others, see [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]), especially for developing countries, although ongoing internationalization efforts in the healthcare sector have posed problems in terms of data security and, therefore, studies conducted on developing countries present limitations in terms of data reliability [27]. Further, human capital is demonstrated to have both external and internal spillover effects on growth [28] and is argued to have an indispensable role in achieving high levels of sustainable economic growth which, according to Organization for Economic Co-operation and Development (OECD), means growth that balances economic, social, and environmental considerations [29].…”
Section: Introductionmentioning
confidence: 99%